MgCeAl11O19:Tb3+ and Mg8Ge2O11F2:Mn4+ in enhancing the color quality of remote phosphor LED - My Hanh Nguyen Thi; Phung Ton That (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
As the name infers, the triple-layer remote phosphor (TRP) has 3 phosphor layers includes the red Mg8Ge2O11F2:Mn4+ phosphor layer on the top, the green MgCeAl11O19:Tb3+ phosphor layer in the middle, and the yellow YAG:Ce3+ layer at the bottom and is mentioned as a solution to increase the chromaticity and luminescence adequacy of the white LEDs (WLEDs) in this article. As to control the red light for higher value achieve in the color rendering index (CRI), using red Mg8Ge2O11F2:Mn4+ phosphor in the TRP structure is recommended. All the outcomes indicate that when red phosphor Mg8Ge2O11F2:Mn4+ concentration grows the CRI gets higher values, and drastically declines when the concentration of green phosphor MgCeAl11O19:Tb3+ increases. As the same time, applying the green MgCeAl11O19:Tb3+ phosphor layer to manage the green light as it can make the luminous efficacy (LE) of WLEDs increase. In particular, the index of LE can also be improved over 40% by limiting the scatter of light and putting in green light. Moreover, to preserve the average correlated color temperature (ACCT) stable at 8500K, the yellow YAG:Ce3+ concentration must be cut down as the concentration of red and green phosphor rise.